2018
DOI: 10.3390/hydrology5020027
|View full text |Cite
|
Sign up to set email alerts
|

Development of Monsoonal Rainfall Intensity-Duration-Frequency (IDF) Relationship and Empirical Model for Data-Scarce Situations: The Case of the Central-Western Hills (Panchase Region) of Nepal

Abstract: Intense monsoonal rain is one of the major triggering factors of floods and mass movements in Nepal that needs to be better understood in order to reduce human and economic losses and improve infrastructure planning and design. This phenomena is better understood through intensity-duration-frequency (IDF) relationships, which is a statistical method derived from historical rainfall data. In Nepal, the use of IDF for disaster management and project design is very limited. This study explored the rainfall variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…Studies have demonstrated that roads are one of the 658 K. Sudmeier-Rieux et al: Invited perspectives: Mountain roads in Nepal at a new crossroads greatest anthropogenic drivers of environmental degradation, erosion and landslides in Nepal (Petley et al, 2007;Froude and Petley, 2018;Vuilliez et al, 2018). This situation is worsening due to the intensifying rainfall during the monsoon, largely attributed to climate change (Petley et al, 2007;Bharti et al, 2016;Devkota et al, 2018;Froude and Petley, 2018), which has led to a greater occurrence of landslides, especially in the middle hills (McAdoo et al, 2018). The possibility of an earthquake of even greater magnitude than the 2015 Gorkha earthquake (M 7.8) raises concerns about poorly designed roads increasing the likelihood of catastrophic landslides (Singh, 2018).…”
mentioning
confidence: 99%
“…Studies have demonstrated that roads are one of the 658 K. Sudmeier-Rieux et al: Invited perspectives: Mountain roads in Nepal at a new crossroads greatest anthropogenic drivers of environmental degradation, erosion and landslides in Nepal (Petley et al, 2007;Froude and Petley, 2018;Vuilliez et al, 2018). This situation is worsening due to the intensifying rainfall during the monsoon, largely attributed to climate change (Petley et al, 2007;Bharti et al, 2016;Devkota et al, 2018;Froude and Petley, 2018), which has led to a greater occurrence of landslides, especially in the middle hills (McAdoo et al, 2018). The possibility of an earthquake of even greater magnitude than the 2015 Gorkha earthquake (M 7.8) raises concerns about poorly designed roads increasing the likelihood of catastrophic landslides (Singh, 2018).…”
mentioning
confidence: 99%
“…To facilitate planning, design and operation of various water management projects against weather events (such as floods, drought) and/or to reduce human and economic losses, there is need to understand the hydrological extremes and their frequency at selected temporal scales [83,84]. This can be through extreme value analysis on the hydrological time series for different aggregation levels, which generates Amplitude-Duration-Frequency (ADF) relationships.…”
Section: Amplitude-duration Frequency Analysesmentioning
confidence: 99%
“…The LSM was verified adopting a receiver operating characteristics (ROC) curve [52,53] utilizing the inventory maps. The research followed a pragmatic approach based on a regional rainfall intensity-duration-frequency (IDF) model, published by Devkota et al (2018) [54], and the soil depth to bed rock (SDTB) [55] of the Phewa Lake watershed. The saturation depth of the soil profile at watershed scale was estimated adopting the Green-Ampt (GA) model according to Dingman (2002) [56], while soil physical and hydrological properties were derived either in the field or in the laboratory.…”
Section: Research Strategymentioning
confidence: 99%
“…The NbS technique implemented in this research was a hybrid type of eco-engineering, encompassing simple civil engineering structures and the plantation of perennial grass species. Civil structural measures such as roadside and surface drainage were designed considering rainfall intensity [54], while civil and geo-technical engineering approaches were adopted for the toe and retaining wall construction. Plantation designs followed Howell (1999b) [59] in diagonal rows, and clusters were maintained for each species.…”
Section: Selection Design and Implementation Of Nbs Techniquesmentioning
confidence: 99%
See 1 more Smart Citation